Livestock input supply and service provision in Ethiopia: challenges and opportunities for market-oriented development - Tegegne, Azage; Gebremedhin, Berhanu; Hoekstra, Dirk (International Livestock Research Institute, 2010)
Livestock production in Ethiopia has, for long, remained subsistence with limited market-orientation and poor institutional support. Producing for the market requires re-orientation of the production system and development of a knowledge based and responsive institutional support services. Institutional support services of extension, research, input supply, rural finance and marketing are key areas of intervention that can play a central role in the transformation of subsistence production into market orientation. Livestock production systems in Ethiopia can be broadly categorized into mixed crop–livestock system, pastoral and agropastoral system, and urban and peri-urban production systems. The demand for institutional support services for livestock development in these production systems can vary significantly. The way extension system is oriented in Ethiopia may not be in the best interest of livestock keepers and lacks the responsive capacity to the demands for livestock services. In fact, most often livestock development issues are left to development projects and NGOs that have limited scope, coverage and duration. The major inputs for livestock development include animal genetic resources, feeds and forages, veterinary drugs, vaccines, machinery equipment and utensils as well as knowledge. Most of these inputs have been supplied only by the government or government sponsored projects. Limited credit facilities to support livestock development have been provided by microfinance institutions, food security projects, small-scale micro enterprises and NGOs.